Growth of low cost carrier and its possible impact in Malaysia's airport terminal developments - Said Khairani, Syed Naqiuddin; Sabar, Rohafiz (2012)
Current trends in the aviation industry have seen the rise of low-cost carrier (LCC) which had given stiff competitions to the traditional airlines. With Malaysia also involved in the emergence of LCC, the research paper aimed to analyze the growth trends that currently experienced in the industry. The growth analysis is identified by examining the worldwide and regional growth trend, before assessing the trend experienced in the country. The research then concluded by analyzing the potential impact of the LCCs growth into the development of airport terminals in Malaysia.